2020
DOI: 10.15283/ijsc19088
|View full text |Cite
|
Sign up to set email alerts
|

miR-450a-5p Eliminates MGO-Induced Insulin Resistance via Targeting CREB

Abstract: Background and Objectives: miR-450a-5p was involved in fat formation, however, its role in insulin resistance remains unclear. This study investigated the effects of miR-450a-5p on endothelial cells, with the aim of finding a potential target for diabetes mellitus. Methods and Results: Human umbilical vein endothelial cells (HUVECs) were treated with low-glucose, high-glucose, methylglyoxal (MGO), and insulin alone or in combination with MGO. The expression of miR-450a-5p in treated cells was measured by quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…Research has identified the potential function of miR-450a in human disease. Upregulated miR-450a eliminated methylglyoxal-induced insulin resistance via targeting cyclic AMP response element binding protein and may therefore be used as a potential target to improve insulin resistance and treat patients with diabetes-associated diseases (33). Furthermore, after glutamine discontinuation, miR-450a overexpression decreased the mitochondrial membrane potential but increased glucose uptake and cell viability, which are characteristic of less invasive cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified the potential function of miR-450a in human disease. Upregulated miR-450a eliminated methylglyoxal-induced insulin resistance via targeting cyclic AMP response element binding protein and may therefore be used as a potential target to improve insulin resistance and treat patients with diabetes-associated diseases (33). Furthermore, after glutamine discontinuation, miR-450a overexpression decreased the mitochondrial membrane potential but increased glucose uptake and cell viability, which are characteristic of less invasive cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that fructose-fed rats for 4 weeks increase the levels of miR-450a-5p in total plasma ( Table S3 ). A recent study showed that the up-regulation of this miRNA improves insulin resistance in non-adipocyte cells ( Wei, Meng & Zhang, 2020 ). On the other hand, we showed that the abundance of miR-21-5p in EVs is high; however, we did not find changes in this miRNA in both cells and rats.…”
Section: Discussionmentioning
confidence: 99%
“…After screening all the miRNAs, we found that 9 downregulated miRNAs and 3 upregulated miRNAs were reported to have the ability to promote the migration of other cells (Fig. 5e) [20][21][22][23][24][25][26][27][28][29][30][31]. Further analysis revealed that 4 downregulated miRNAs were reported to regulate the NF-κB signaling pathway (Fig.…”
Section: Dp7-c and The Metabolite Pa Promoted DC Migration By Upregulating The Chemokine Receptor Cxcr2mentioning
confidence: 99%